Analisis Film Dilan 1990 dari Sudut Pandang Regulasi Penyiaran - Muhammad Jihad Pranata Gunawan; Harmonis Harmonis (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This study is entitled "Analysis of the Film Dilan 1990 from the Perspective of Broadcasting Regulation". The phenomenon that occurred in the Film Dilan 1990 became an identification for today's teenagers, this film is categorized as a romance film that teaches how to communicate well and respect, it is undeniable that there are scenes of verbal and non-verbal violence, this is a violation and limitation of violent scenes in the second part of article 24 according to P3SPS. This study aims to analyze and examine the violence and love contained in the Film Dilan 1990 from the perspective of P3SPS. The main theory used in this study is broadcasting, film, television, P3SPS. The method used in this study uses qualitative analysis. Data collection techniques are carried out by interviews, observation and documentation. The results of this study indicate that the violence that occurs in the Dilan 1990 film from the perspective of P3SPS is violence and representation of love carried out by the actors in the Dilan 1990 film. The conclusion depicted in the Dilan 1990 film teaches everyone to always be responsible for the people they love, be kind to others and not differentiate between each other and not liking does not mean having to hate.customers.